Stability of, and Associations Between, Parent and Child Locus of Control Expectancies - Nowicki, Stephen; Iles-Caven, Yasmin; Gregory, Steven; Ellis, Genette; Golding, Jean (Frontiers in Psychology, 2018)
The purpose of the present study was to assess the stability of locus of control (LOC) scores over time using data gathered from tests constructed to be consistent with Rotter’s definition of locus of control. We compared LOC scores of parents (measured prior to the birth of the index child and at 6 years and 18 years later) and their offspring (at ages 8 and 16) to explore how stable adult and child LOC was over time and to see how parental LOC was associated with the LOC of the child aged 8 and again at 16. Locus of control was measured using modified versions of adult (ANSIE, Nowicki & Duke, 1974) and child (CNSIE, Nowicki & Strickland 1973) locus of control scales, administered to participants in the Avon Longitudinal Study of Parents and Children (ALSPAC) in the United Kingdom. We predicted that: (1) adult scores would be more stable than children’s and (2) parents’ and children’s LOC scores would be related to one another. Analyses of the data found that individual’s LOC scores were significantly associated over time, with adult scores (r ~ 0.50) more highly correlated than children’s (r ~ 0.20). Correlations suggest more stability for adults than children, but also indicate the occurrence of substantial change across time. Although statistically significant, correlations between family members were small at both childhood and adolescent time points. Additional analyses suggested that mother and father locus of control scores were more highly correlated with opposite rather than with same sex children, but again though significant the coefficients were small. We also analyzed the binary outcomes of externality to assess the contribution of parental contributions to externality in the 8 and 16-year-old children and found correlations were significant, but small. Possible explanations are offered for why the associations between parent and child LOC were not higher. We concluded that researchers need to focus more on clarifying how children’s LOC is acquired.